PENERAPAN MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA WHEEL OF WORDS MATERI HOMONIM TERHADAP HASIL BELAJAR SISWA DI KELAS IV SD NEGERI 1 BEUREUNUEN KABUPATEN PIDIE - Sova Zahara; Linda Vitoria; Hasniyati Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students' low understanding of homonyms is one of the problems in learning Indonesian in elementary schools. Based on initial observations in grade IV of SD Negeri 1 Beureunuen, some students still have difficulty in distinguishing the meaning of homonyms based on the context of the sentence, so that the learning outcomes have not reached the established Learning Objective Achievement Criteria (KKTP). This study aims to describe the activities and learning outcomes of students through the application of the Teams Games Tournament (TGT) learning model assisted by Wheel of Words media on the material of homonyms. This study uses a descriptive qualitative approach. The subjects of the study were 28 grade IV students of SD Negeri 1 Beureunuen. Data collection techniques were carried out through observation and learning outcome tests. Data were analyzed descriptively by calculating the percentage of student activity and the completeness of learning outcomes. The results showed that student learning activities were in the good category with an average score of 25.54 out of a maximum score of 32. The highest percentage of activity was found in the learning readiness indicator at 100%, while the active answering and learning participation indicators were each at 73.21%. Student learning outcomes showed a class average score of 79.36 with a learning completion percentage of 75%, or 21 out of 28 students had achieved the KKTP. The research findings indicate that the implementation of the TGT learning model assisted by Wheel of Words media can create more active and engaging learning, as well as support the achievement of student learning outcomes on homonyms.